Essays on the cost effects of airline mergers and alliances - Le, Huubinh B. (Kansas State University, 2014)
My dissertation is comprised of two essays in the field of industrial organization with an emphasis on the airline industry. In particular, I investigate how airline mergers and alliances affect the components of total cost. By using a methodology that does not require the researcher to have cost data, I am able to infer marginal costs, fixed costs and sunk costs changes associated with mergers and alliances. My first essay examines two recent airline mergers—Delta/Northwest and United/Continental. Most post-merger analysis in airlines disproportionately focuses on assessing price rather than cost changes. Perhaps one reason is that reliable price data are more readily available. Despite the difficulty of obtaining cost data, researchers have sought to empirically assess whether cost efficiency gains associated with a merger outweigh the increased market power of the merged firm. The results from my analysis suggest that both mergers are associated with marginal and fixed costs savings, but higher market entry costs. The magnitude of the cost effects differed across the mergers. Moreover, I find that the market power effects of these mergers were negligible. My second essay investigates the cost effects of the codesharing alliance between Delta, Northwest and Continental Airlines. Codesharing is one of the most popular forms of airline cooperation that allows an airline to market and sell seats on its partners’ flights as though it owns those flights. Studies have found that airline alliances have very little to no effect on total cost. Rather than analyzing cost as a whole, I study whether a disaggregate analysis on cost is more appropriate. I find evidence that forming an alliance helps generate more passenger traffic for the alliance partners thereby reducing the partner carriers' marginal cost. Even though the literature has found that the total cost effects to be small, an alliance can have a considerable impact on some components of cost.
Keywords: Cost efficiencies; Airline mergers; Airline alliance; Economics (0501)